The Influence of Transformasional Leadership Style, Organizational Climate and Work Environment on Productivity through Work Motivation at PT. Sumatra Tobaco Trading Company - Ananda, Novita; Lumbanraja, Prihatin; Absah, Yeni (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of transformational leadership, organizational climate, and work environment on work productivity, with work motivation as a mediating variable. Using a quantitative approach, data were collected through questionnaires and documentation from 100 production employees selected using saturated sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results show that the work environment has the strongest direct positive and significant effect on work productivity. Additionally, work motivation significantly mediates the effects of transformational leadership, organizational climate, and work environment on productivity. Among the mediating paths, organizational climate has the most substantial indirect effect on productivity through work motivation. These findings highlight the importance of a supportive organizational climate and motivated workforce in enhancing productivity.